2006
DOI: 10.1111/j.1365-2362.2006.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of imatinib mesylate on human haematopoietic progenitor cells

Abstract: This study suggests that imatinib exerts myelosuppressive effects through inhibition of haematopoietic progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In vivo and in vitro evidence suggests that imatinib mesylate may directly inhibit normal hematopoiesis. 39,40 In our present study, we found that inhibition of PDGFR by imatinib mesylate inactivates PI3-k/Akt signaling and PDGF-induced anti-apoptosis in megakaryocytes. This suggests that blockade of PDGFR by imatinib mesylate may reduce megakaryocytopoiesis leading to thrombocytopenia, highlighting a crucial role for PDGF receptors in megakaryocytopoiesis.…”
Section: Discussionsupporting
confidence: 58%
“…In vivo and in vitro evidence suggests that imatinib mesylate may directly inhibit normal hematopoiesis. 39,40 In our present study, we found that inhibition of PDGFR by imatinib mesylate inactivates PI3-k/Akt signaling and PDGF-induced anti-apoptosis in megakaryocytes. This suggests that blockade of PDGFR by imatinib mesylate may reduce megakaryocytopoiesis leading to thrombocytopenia, highlighting a crucial role for PDGF receptors in megakaryocytopoiesis.…”
Section: Discussionsupporting
confidence: 58%
“…Cells were washed, and were then grown in a methylcellulose culture essentially as described. 31 In brief, cells were seeded in 35 mm culture plates (2-5¥10 5 per well in triplicates) at 37°C (5% CO2) in 0.8% methylcellulose with 30% FCS, 10% bovine serum albumin (Gibco, Carlsbad, CA, USA), alphathioglycerol, GM-CSF (10 ng/mL) (R&D Systems, Minneapolis, MN, USA), IL-3 (5 ng/mL) (R&D), and erythropoietin (2 U/mL) (Roche, Basel, Switzerland). After 14 days, the numbers of CFU-GM, BFU-E, and CFU-GEMM were counted under an inverted microscope (Olympus, Tokyo, Japan).…”
Section: Clonogenic Assay and Evaluation Of Long-term Growth Of Leukementioning
confidence: 99%
“…32 Drug interactions were determined by calculating combination index (CI) values using Calcusyn software (Calcusyn; Biosoft, Ferguson, MO, USA). 30,31 A CI of less than 1 indicates synergy, a CI of 1 indicates additive effects, and a CI of more than 1 is indicative of antagonistic effects.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…it is well-known a suppressive role of imatinib on the normal progenitor marrow cells [12,13] which is capable to induce at treatment start (when normal marrow cells are reduced) an early "acute" hematologic toxicity, usually reversible with progressive elimination of Ph1 cells and re-expansion of normal progenitor cells; after prolonged treatment in responsive patients, when almost all marrow progenitor cells are normal, imatinib could maintain its suppressive effect in a chronic way, with a less significant but prolonged clinical effect of chronic anemia. 2. at least for cases of chronic anemia with features of iron deficiency, imatinib could interfere with iron absorption and/or metabolism, leading to a condition of oral iron resistance.…”
Section: Discussionmentioning
confidence: 99%